TRANSFORMASI INOVASI PRODUK DAN PENGEMBANGAN SDM BERKELANJUTAN BAGI UMKM KOTA METRO-LAMPUNG - Indriyani, Susi; Bakti, Umar; Yusda, Desi Derina; Loliyani, Rini; Wardana, Made Ali (Penerbit Widina, Widina Media Utama, 2025)
This Community Service (PkM) aims to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Metro City, Lampung, through intensive training in product innovation strategies and sustainable Human Resource Development (HRD). A total of 25 MSME actors from the culinary and craft sectors participated in the three-day activity. The PkM methods included focus group discussions (FGD), material delivery, product innovation design workshops, and post-training mentoring. The evaluation results showed a significant increase in participants' understanding of the importance of product differentiation (35%) and the concept of sustainable HRD (40%). Participants successfully identified at least one new strategic product innovation idea and developed a Simple Employee Development Plan Framework (RPKS). This success indicates that interventions focusing on strategic planning and Human Capital are highly effective in preparing MSMEs to face dynamic market challenges. This training provides a tangible contribution to fostering innovative MSMEs in Metro City with a strong HR foundation for long-term growth, ensured by the formation of the